PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENUMBUHKAN KEMANDIRIAN BELAJAR PADA SISWA SMK KELAS XI - Fitria Sofianti; M. Afrilianto (IKIP Siliwangi, 2021)
The purpose of this observation is to find out whether the application of a scientific approach can help students to be more independent in learning, given that there are still passive students and a lack of enthusiasm and independence ion learning. The method used is the method of assignment and question ad answer. The population in this observation was students at one of the private vocational schools in Cimahi City and the sample was taken from 35 class XI students. The instrument used was an essay test consisting of six essay questions with a pretest, posttest, stage equipped with a questionnaire instrument consisting of 14 statements positive and 14 negative statement and interviews. The data processing technique used is triangulation technique, which combines various data processing techniques. Based on the research that has been done, the results of the application of the scientific approach show that there are changes in student learning that are more independent.